Nematofauna edáfica em sistemas de uso do solo na microrregião de Chapadinha-MA - Doihara, Izumy Pinheiro [UNESP] (2015)
The edaphic nematofauna is a group of organism's inhabitants of the land belonging to the nematode phylum. The biological activity of soil organisms such as the nematode is of great importance for the maintenance of the quality and fertility of the soil. Soil management activities and vegetation contribute to change the biological activities, the physical and chemical characteristics of the soil and especially the structure and composition of nematode communities. The nematodes are present in a large number, are sensitive to various changes in soil conditions and the ease its extraction from the soil, have been used to assess the quality of the soil and agricultural systems. This study aimed to describe the trophic structure, diversity and composition of nematofauna in different land use systems and associate the edaphic nematofauna the chemical and physical properties in five land use systems (alley cropping, cultivation under slash and burn, native forest, soy cultivation and pasture farming) located in the micro-region of Chapadinha the state of Maranhão. Samples were collected between the months of October 2013 and June 2014 (corresponding to the dry and rainy seasons), and at three depths (0 - 0.1 m; 0.1 - 0.2 m and 0.2 - 0.3 m). The nematodes were extracted by centrifugal flotation method in sucrose solution and identified to genus level. The physical and chemical analyzes of soil were performed following usual methods. For all studied environments calculated up: abundance, richness and diversity indices. The effect of seasonality in nematofauna was analyzed using Mann-Whitney nonparametric test and the results regarding the association of physical and chemical variables with the genera of nematodes were analyzed by means of multivariate principal component analysis. In total, 60 genera were identified; they ranged between 10-46 environments. Identified nematodes, 39.39% are plant parasites, 24.59% bacteriophages ...